Modularity in ecological networks between frugivorous birds and congeneric plant species. (31st August 2016) - Silva, Adriano M.; Maruyama, Pietro K.; Paniago, Luís Pedro M.; Melo, Celine
Abstract: Ecological and evolutionary factors influence the presence of modules in species interaction networks, and these modules usually cluster functional similar species. But whether closely related species form modules is still unknown. We tested whether the interaction networks formed by frugivorous birds and Miconia plants are modular and evaluated how modules were divided. To do so, we gathered from the literature data concerning four networks of Miconia and their frugivorous birds (three from Brazilian savanna and one from a rain forest in Panama). We quantified modularity using binary and weighted algorithms and also tested the relationship between bird traits (body mass, dietary specialization, migratory behaviour and phylogeny) in relation to within- and among-module connectivity indices ( c and z values). If considering only binary information, networks did not present distinct modular structure. Nevertheless, by including interaction strength, modules can be detected in all four Miconia- bird networks. None of the bird traits, however, was related with the connectivity indices. The possible fluctuation of frugivorous bird abundance coupled with the asynchronic fruiting period of Miconia might favour the formation of temporal modules comprising birds and plant species with phenological overlap, ensuring seed dispersal and facilitating the coexistence in sympatry. Bird traits had little effect on the role that each species plays within the modular network, probably because the frugivorous assemblages were dominated by small-bodied and opportunistic species.